Formulasi Granul Mukoadhesif Dispersi Padat Ketoprofen-Pvp K-30 Menggunakan Kitosan - Salman, Salman; Meryza, Meryza; Noviza, Deni (Jurnal Sains dan Teknologi Farmasi, 2013)
A study on mucoadhesive properties of ketoprofen â PVP K-30 solid dispersion granules using chitosan had been done. Solid dispersion of ketoprofen and PVP K-30 was made at ratio 1:1 using solvent method. Granules were made by wet granulation method at various concentrations of chitosan (10%, 20% and 30%). The granules were evaluated including photomicroscopy, flow rate, angle slides, water content, particle size distribution, dissolution test, in-vitro test bioadhesif and wash off test. The release of ketoprofen from the granules was determined using basket dissolution test in pH 7.5 phosphate buffer medium for 8 hours. Mucoadhesive properties were tested by in-vitro bioadhesif tests and wash off test. The dissolution test showed the dissolution effeciency value of formula 1, 2, and 3, respectively, was 78.9890 Â± 1.1398; 77.3889 Â± 1.4312, and 75.8869 Â± 0.2210 %. Results showed a decrease in the release of the active substance from the granules, with the increase in chitosan concentration. Statistical analysis of the efficiency of dissolution showed a significant difference among the three formulas with (P <0.05). In vitro bioadhesif tests showed that granules were able to attached to the stomach and intestinal mucosa of rabbits.